2018
DOI: 10.1038/s41598-018-25364-1
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid compositions contribute to the proteins’ evolution under the influence of their abundances and genomic GC content

Abstract: Inconsistent results on the association between evolutionary rates and amino acid composition of proteins have been reported in eukaryotes. However, there are few studies of how amino acid composition can influence evolutionary rates in bacteria. Thus, we constructed linear regression models between composition frequencies of amino acids and evolutionary rates for bacteria. Compositions of all amino acids can on average explain 21.5% of the variation in evolutionary rates among 273 investigated bacterial organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Coincidentally, the atp8 and cox1 genes were found to have the highest (0.63) and lowest (0.05) Ka/Ks values, respectively. These results indicated that the evolutionary rate of proteins are related to their nucleotide composition, which is consistent with the view of Du et al (2018). G+C content influences amino acid compositions, and then changes the proteins’ evolution (Jordan et al 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Coincidentally, the atp8 and cox1 genes were found to have the highest (0.63) and lowest (0.05) Ka/Ks values, respectively. These results indicated that the evolutionary rate of proteins are related to their nucleotide composition, which is consistent with the view of Du et al (2018). G+C content influences amino acid compositions, and then changes the proteins’ evolution (Jordan et al 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Amino acid composition is an important parameter that reveals physiological function, existence, and evolutionary trends of an organism (Du et al 2018;Zhu et al 2019). Variation in the genomic GC content affects the amino acid composition and thus influences the codon usage pattern (Herbeck et al 2003;Uddin and Chakraborty, 2019).…”
Section: Analysis Of Amino Acid Compositionmentioning
confidence: 99%
“…So far, more than ten statistical methods have been introduced to detect the molecular footprints that resulted in natural selection [4,5]. Of these, the method of Ka/Ks ratio (Ka: the number of non-synonymous substitutions per non-synonymous site, and Ks: the number of synonymous nucleotide substitutions per synonymous site) has a great impact on estimation of selection pressure and understanding the evolutionary dynamics of proteincoding sequences across closely related and yet diverged species [6][7][8].…”
Section: Introductionmentioning
confidence: 99%